Satellite cell activation and retention of muscle regenerative potential after long-term denervation. (30th December 2020) - Wong, Alvin; Garcia, Steven M.; Tamaki, Stanley; Striedinger, Katharine; Barruet, Emilie; Hansen, Scott L.; Young, David M.; Pomerantz, Jason H.
Abstract: Irreversible denervation atrophy remains an unsolved clinical problem, and the role of skeletal muscle stem cell (MuSC, satellite cell) depletion in this process is unclear. We investigated the ability of MuSCs to regenerate muscle in the context of denervation. Three to 12 months following sciatic denervation in mice, MuSC number, size, EdU uptake, rate of division, and mitochondrial activity were increased. Following acute myotoxin injury, denervated muscles formed new muscle fibers in situ. MuSCs isolated via flow cytometry from denervated mouse muscle, or from atrophic denervated gluteus maximus muscles of humans with complete spinal cord injuries two decades prior, formed new muscle fibers and reoccupied the anatomic niche after transplantation into uninjured muscle. Our results show unequivocally that, even after prolonged denervation, MuSCs retain intrinsic regenerative potential similar to that of uninjured MuSCs. Treatment of denervation atrophy will require elucidating the non-MuSC environmental changes in muscle that prevent functional regeneration. Abstract : Human satellite cells isolated from gluteus maximus muscle denervated >20 years retain the ability to engraft and form new muscle fiber when transplanted into NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice, and also reoccupy the anatomic niche. Left: NSG muscle showing human dystrophin (green) and laminin (red). Right: NSG muscle showing costaining of human lamin A/C (red) Pax7 (green). Laminin (grey), 4′, 6-diamidino-2-phenylindole (DAPI, blue) counterstain.